2015
DOI: 10.1039/c5ra14174e
|View full text |Cite
|
Sign up to set email alerts
|

A new fluorescent pH probe for acidic conditions

Abstract: A new fluorescent probe based on imidazo[1,5-a]pyridine probe for low pH was synthesized and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 46 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…11 A variety of techniques including nuclear magnetic resonance, HPLC-MS acid-base indicator titration, absorption spectroscopy, and electrochemistry have been reported to measure pH values. [12][13][14][15] An optical probe, especially a uorescent probe, is one of the most powerful tools for detecting pH in cells for its advantages of simple operation, high sensitivity, and temporal resolution. [16][17][18] Many pH uorescent probes have been designed.…”
Section: Introductionmentioning
confidence: 99%
“…11 A variety of techniques including nuclear magnetic resonance, HPLC-MS acid-base indicator titration, absorption spectroscopy, and electrochemistry have been reported to measure pH values. [12][13][14][15] An optical probe, especially a uorescent probe, is one of the most powerful tools for detecting pH in cells for its advantages of simple operation, high sensitivity, and temporal resolution. [16][17][18] Many pH uorescent probes have been designed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, successful applications of small chemical molecules in inhibiting senescence in BMSCs by maintaining lysosomal functions provide potential intervention strategies to prevent body from aging and regenerate tissues [ 28 ]. Our previous work showed that a novel small molecule, 3-butyl-1-chloro imidazo [1, 5-a] pyridine-7-carboxylic acid (SGJ), had been demonstrated as a fluorescent probe to selectively and sensitively respond to acidic pH with fast response (within 3 min) [ 29 ]. Here, we wish to report our studies on SGJ, in which clarify its functions in lysosomes, relationship with Baf-A1 and role in suppressing cell senescence.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of neutral form, the dihedral angle between benzene ring and hemicyanine skeleton is only 0.30°, while the protonated form displayed a larger dihedral angle as 9.84°. Such higher energy gap and less structural rigidity of 1 + H + could be attributable to blue shift in the absorption spectra observed …”
Section: Resultsmentioning
confidence: 99%